2020
DOI: 10.1139/bcb-2019-0364
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1180 promotes cardiomyocyte cell cycle re-entry after injury through the NKIRAS2–NFκB pathway

Abstract: Heart failure (HF) is associated with a considerable number of symptoms and significantly impaired health for humans, including reduced quality of life and physical functioning. Previous studies have indicated that miRNAs have important roles in regulating the development of HF. MiR-1180 is involved in the proliferation, migration, invasiveness, and chemoresistance of cancer cells; however, the underlying mechanisms and role of miR-1180 in the functioning of cardiomyocytes remains unclear. In this study, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Ding et al investigated the miR-1180 mechanism on cardiomyocytes and found that the miR-1180 observed in the rat's heart at embryonal day 9.5 decreased over time and completely disappeared at the seven postnatal days ( 34 ). In H/R-induced cardiomyocytes, miR-1180 expression was downregulated.…”
Section: Characterization Of Cardiomyocyte Proliferationmentioning
confidence: 99%
“…Ding et al investigated the miR-1180 mechanism on cardiomyocytes and found that the miR-1180 observed in the rat's heart at embryonal day 9.5 decreased over time and completely disappeared at the seven postnatal days ( 34 ). In H/R-induced cardiomyocytes, miR-1180 expression was downregulated.…”
Section: Characterization Of Cardiomyocyte Proliferationmentioning
confidence: 99%
“…PTEN/PI3K/AKT is another signal transduction pathway that is activated by miR-301a to promote cardiomyocyte re-entry into the cell cycle; miR-301a suppresses PTEN to activate AKT and induce expression of cell cycle genes such as cyclin D1, in cardiac myocytes [50]. Other miRNAs have been reported to promote cell cycle progression in cardiomyocytes by targeting the TBX1/JAK2/STAT1 pathway [74], the NFkB pathway [75], or signaling molecules such as the cell cycle inhibitors Wee1 [76] and Bim [77], among others [78,79]. These studies suggest that MiRNAs possess the potential for replenishing cardiomyocyte numbers in injured hearts.…”
Section: Selective Induction/inhibition Of Gene Expression Can Induce Cell Cycle Re-activation In Cardiac Myocytesmentioning
confidence: 99%
“…However, the Nodal sig ing pathway, an important signal transduction pathway active during embryonic h development [40], is suppressed by miR-33a-5p which targets nodal modulat (NOMO1) [41]. 92, miR-19a/b or miR-221-3p [33][34][35] or silenced by miR-208a and miR-489, which b phosphoinositide 3-kinase (PI3K) and spindlin-1 (SPIN1), respectively [36 Conversely, other pathways appear to be regulated only by pro-proliferative or apoptotic miRNAs, such as the NF-kB pathway which can be activated by blockade of suppressor of cytokine signaling 3 (SOCS3) and the NF-kB inhibitor interacting Ras-li (NKIRAS2) by miR-324 [38] and miR-1180 [39], respectively. However, the Nodal sig ing pathway, an important signal transduction pathway active during embryonic h development [40], is suppressed by miR-33a-5p which targets nodal modulato (NOMO1) [41].…”
Section: Introductionmentioning
confidence: 99%